Reduction of the toxicity and mutagenicity of alkylating agents in mammalian cells harboring the Escherichia coli alkyltransferase gene. - Brennand, J (1986)
The toxic, mutagenic, and carcinogenic effects of alkylating agents have been attributed to their ability to damage DNA. Reaction at the O6 position of guanine results in miscoding during DNA replication, has been shown to be mutagenic in both bacteriophage and bacteria, and may be responsible for malignant transformation. In common with many other prokaryotes and eukaryotes the Escherichia coli B strain contains a protein that repairs O6-alkylation damage in DNA by transferring the alkyl group to one of its own cysteine residues. We have recently cloned the E. coli O6-alkylguanine alkyltransferase gene and shown it to encode a 37-kDa protein containing an additional activity that removes alkyl groups from alkylphosphotriesters in DNA. To examine the biological effects of this gene in mammalian cells, we have now inserted the coding sequence into a retrovirus-based selectable expression vector and transfected it into Chinese hamster V79 cells that lack endogenous alkyltransferase activity. A clone expressing high levels of the bacterial protein was selected and shown to produce a 37-kDa alkyltransferase protein and to rapidly repair O6-methylguanine produced in the host genome following exposure to N-methyl-N-nitrosourea. In comparison with a control population, this clone is considerably more resistant to the toxic and mutagenic effects of alkylating agents that react extensively with oxygen atoms in DNA. The usefulness of these clones in examining the role of DNA alkylation and other biological effects of alkylating agents is discussed.